Enhancement of the Ceftazidime Efficacy through Cutting-Edge Modifications and In Silico Repurposing against Multidrug Resistance in Pseudomonas Aeruginosa - Shabbir, Muhammad Aqib; Abid, Emmania; Tanveer, Laiba; Absar, Mahnoor; Tariq, Mahnoor; Alvi, Areesha (Current Trends in OMICS, 2025)
Pseudomonas aeruginosa causes acute and chronic infections in patients hospitalized after surgery, heat burns, and other injuries. Different antibiotics are used to treat bacterial infections. A commonly used cephalosporin, namely ceftazidime, shows a significant effect against P. aeruginosa. Ceftazidime targets penicillin-binding protein in P. aeruginosa. Currently used antibiotics are facing resistance due to different mechanisms. Targeting the mutated penicillin-binding protein 3 of P. aeruginosa, this study aims to improve the binding affinities of ceftazidime by adding various functional groups in methylpridinium ring. In silico tools were used to modify the structure of ceftazidime to make it effective against the resistant strains of P. aeruginosa. The 3D structures of normal and mutated penicillin-binding proteins were retrieved from Protein Data Bank (PDB). The structure of the antibiotic was retrieved from PubChem and EMBL-EBI, which was modified through Chemsketch. Azide and phenyl carbonyl groups were added in the methylpridinium ring of ceftazidime. AutoDock Vina was used to visualize the binding affinities of the engineered ceftazidime with proteins. PyMOL was used for visualization. The binding affinity of the engineered ceftazidime was improved upto -8.9 kcal/mol. Simulation analysis of the complex showed its eigenvalue and covariance. The feasibility of the modified structures was verified using SwissADME. ADMET analysis confirmed that these structures remain feasible for utilization after clinical trials. The above modifications allow a better treatment of infections caused by stronger and resistant P. aeruginosa strains. Further analysis needs to be carried out in order to improve other antibiotics and different conjugates for the effective treatment of infections caused by this bacteria.